KOMBINASI HERBA SELEDRI (Apium graveolens, L) DAN DAUN LIDAH BUAYA (Aloe vera, L) SEBAGAI MINUMAN HERBAL INSTAN - Cahyanto, Heru Agus (Kementerian Perindustrian, 2014)
The purpose of this study was to determine the quality of herbal raw materials and consumer acceptability to the instan tea. Celery and aloe vera leaf have an ability to lower blood pressure. The combination of these two herbs are expected to have a synergistic effect in this instant tea. The formulation tea showed the appropriate with the requirements and no difference in taste, color and odor in statistic of the three formulations.Keywords: formulation, celery, aloe vera